2016
DOI: 10.1108/jfmpc-02-2016-0008
|View full text |Cite
|
Sign up to set email alerts
|

Structural equation modelling of construction bond administration

Abstract: Purpose The purpose of this paper is to examine construction bonds, which is a risk management tool for ensuring that projects are delivered successfully, with emphasis on the influence of stakeholders, project characteristics and bonding decision factors. Design/methodology/approach Using case study of completed public building projects, questionnaires were administered on stakeholders that participated in the projects to solicit information on identified issues. Structural equation modelling (SEM) was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…The usage of SEM has gained ground across several disciplines (Hui and Zheng, 2010) to analyze variables and underlying theoretical constructs (Hwang et al , 2010). Oke and Ogunsemi (2016) suggest three SEM approaches that are dependent on the adapted softwares. They are covariance-based modeling (CB-SEM), variance-based modeling (partial least squares) and generalized structured component analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The usage of SEM has gained ground across several disciplines (Hui and Zheng, 2010) to analyze variables and underlying theoretical constructs (Hwang et al , 2010). Oke and Ogunsemi (2016) suggest three SEM approaches that are dependent on the adapted softwares. They are covariance-based modeling (CB-SEM), variance-based modeling (partial least squares) and generalized structured component analysis.…”
Section: Methodsmentioning
confidence: 99%
“…They are covariance-based modeling (CB-SEM), variance-based modeling (partial least squares) and generalized structured component analysis. Some of the reasons for adopting CB-SEM include: suitability for non-experimental research; questionnaire-based social science research studies that are ordinal in nature; and avoidance of excessive multicollinearity which may be present in other statistical techniques Oke and Ogunsemi (2016). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For indicator reliability, the square of factor loadings of each individual indicator was examined and it was observed that almost all the indicators had values nearer to the acceptable minimum value of 0.7 (Oke and Ogunsemi, 2016); however the values, as shown in Table IV, were larger than 0.4, which was considered as the minimum threshold for exploratory research of this nature (Hulland, 1999). The model showed that all the individual constructs had internal consistency higher than the acceptable 0.70; the composite reliability values ranged from 0.83 to 0.95 for the latent constructs.…”
Section: Wlb and Organisational Performancementioning
confidence: 99%
“…Hassan and Adnan (2018) assessed the problems and abuse of performance bond in the construction Industry of Malaysia and found that the lack of uniformity and inconsistency in the contents of guarantee/bond forms results from the one-sided interpretations found in the contracts. Oke and Ogunsemi (2016) carried out a study aimed at examining the effect of stakeholders, project characteristics and bonding decision factors on the administration of construction bonding using structural equation modelling within Lagos and Ondo states; and found that these variables have an effect on the success of bonded construction projects.…”
Section: Independent Journal Of Management and Production (Ijmandp)mentioning
confidence: 99%